Synthesis of nanometric β-barium metaborate powder from different borate solutions by ultrasound-assisted precipitation - Aksener, Eymen; Figen, Aysel Kanturk; Piskin, Sabriye (SPRINGER, 2014)
In this study, the synthesis of barium metaborate powder (BaB2O4) was carried out by ultrasound-assisted precipitation using different borate solutions. Different solutions such as borax (Na2B4O7, BD), boric acid (H3BO3, BA), and sodium metaborate (NaBO2, SMB) were used in the synthesis and an ultrasonic immersion horn probe was used as the major source of ultrasound. The effect of reaction temperature and time, pH, and crystallization time on the BaB2O4 yield (%) was investigated. The ultrasound-assisted synthesis up to 90 % yield could be achieved using a 0.2 M BD solution at 80 A degrees C, reacting for 5 min at pH 13 followed by 2 h of crystallization. Following crystallization, the obtained powder was heated up to 140, 250, 650, and 750 A degrees C for 2.5 h, and it was shown that beta-BaB2O4 nanometric powders were obtained after the 750 A degrees C heat treatment.
Keywords: Barium metaborate; Ultrasound; Borate solution; Precipitation synthesis; BETA-BAB2O4; GROWTH; CRYSTALS; BBO; SYSTEM; Chemistry